Estimating Geographical Variation in the Risk of Zoonotic Plasmodium knowlesi Infection in Countries Eliminating Malaria - Shearer, Freya M.; Zhi, Huang; Weiss, Daniel J.; Wiebe, Antoinette; Gibson, Harry S.; Battle, Katherine E.; Pigott, David M.; Brady, Oliver J.; Chaturong, Putaporntip; Somchai, Jongwutiwe; Yee, Ling Lau; Magnus, Manske; et al. (PLOS, 2016)
Plasmodium knowlesi is a malaria parasite found in wild monkey populations and transmitted from this animal reservoir to humans via infected mosquitoes. It causes severe and fatal disease in humans, and is the most common cause of malaria in parts of Malaysia. The geographical distribution of this disease is largely unknown because it is often misdiagnosed as one of the human malarias. Human malaria parasites are primarily transmitted between humans via mosquitoes and are not frequently transmitted from other animals to humans. Many countries in Southeast Asia, where P. knowlesi infections have been reported, are making progress towards eliminating the human malarias. Understanding the geographical distribution of P. knowlesi is important for identifying areas where malaria transmission will continue after the human malarias have been eliminated. In locations that have high volumes of P. knowlesi infection data, we modelled patterns of variation in the data linked to environmental predictors, and used this to estimate P. knowlesi infection risk in locations where data is lacking. The resulting map represents an initial evidence-base for identifying areas of human disease risk that should be prioritized for surveillance, particularly in the context of malaria elimination in the region.